Beban Keluarga Pada Penderita Diabetes Melitus Tipe II - I Ketut Alit Adianta; Gusti Ayu Wardianti (Jurnal Riset Kesehatan Nasional, 2018)
ABSTRACTDiabetes mellitus (DM) is chronic disease characterized by blood glucose level high than normal. When one of family member suffers from illness, it will affect family condition in managing treatment and caring.This study aimed to identify family burden of patients with Type II DM in Puskesmas III of North Denpasar including objective, subjective, and iatrogenic burden. This study employed descriptive design with cross sectional approach. The study involved 102 respondents with consecutive sampling. Data were collected by questionnaire. Findings indicated that objective burden of family with mild, moderate, and heavy burden were 24.5%, 8.8% and  66.7%; respectively). Subjective burden indicating mild, moderate, and heavy burden were 6.9%, 70.6% and 22.5% respectively. Iatrogenic burden indicating mild, moderate, and heavy burden were 8.8%,  1% and 90.2% respectively. All families experienced heavy burden in caring for patients with DM because of difficulty in treatment.  Keywords: Objective Burden, Subjective Burden, Iatrogenic Burden, Diabetes Mellitus